2020
DOI: 10.1021/acsami.0c13236
|View full text |Cite
|
Sign up to set email alerts
|

Band-Edge Engineering To Eliminate Radiation-Induced Defect States in Perovskite Scintillators

Abstract: Under radiative environments such as extended hard Xor γ-rays, degradation of scintillation performance is often due to irradiation-induced defects. To overcome the effect of deleterious defects, novel design mitigation strategies are needed to identify and design more resilient materials. The potential for band-edge engineering to eliminate the effect of radiation-induced defect states in rare-earthdoped perovskite scintillators is explored, taking Ce 3+ -doped LuAlO 3 as a model material system, using densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…According to the theoretical DFT computations in ref. 32 , the conduction band edge of GdAP should be lowered by ~2.5 eV compared to that of LuAP. Therefore, the decreasing edge of the conduction band should effectively cover all the mentioned shallow electron traps, provided that the positions of the traps remain unchanged.…”
Section: Energy Transfer Processes In Pl: the Modelmentioning
confidence: 95%
See 2 more Smart Citations
“…According to the theoretical DFT computations in ref. 32 , the conduction band edge of GdAP should be lowered by ~2.5 eV compared to that of LuAP. Therefore, the decreasing edge of the conduction band should effectively cover all the mentioned shallow electron traps, provided that the positions of the traps remain unchanged.…”
Section: Energy Transfer Processes In Pl: the Modelmentioning
confidence: 95%
“…Notably, a recent theoretical study, which used density functional theory, focused on the possibility of eliminating the effects of radiation-induced damage by bandgap engineering the LuAP:Ce scintillator 32 . The above study examined the role of the Ga admixture at the Al site and found that LuGaO 3 should have a bandgap that was more than 2 eV smaller than that of LuAlO 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where the HSE06 hybrid functional is used for final electronic structure calculations, we use 33% exact exchange instead of the usual 25%. 78 The screening parameter is 0.2 Å À1 . In all cases, we maintain a minimum momentum space resolution of 0.7 Å À1 .…”
Section: Computationalmentioning
confidence: 99%
“…For example, to mitigate the effects of traps, either defect engineering [32], with the goal of eliminating the defects responsible for the traps, or band-edge engineering [7] to eliminate the effects of the traps, can improve transport processes. These kinds of efforts have improved the light output in garnets almost 5-fold [29,31] and seem promising for perovskites as well [25]. However, even if all traps, or their effects, are eliminated, there is a chance that the carriers escape the local region and are thus unable to recombine and scintillate.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%